Optic Neuritis After Viral Vector versus mRNA COVID-19 Vaccines: A Systematic Review and Comparative Meta-Analysis - Tiara Alexander; I Made Ady Wirawan; I Gusti Ayu Made Juliari; Ida Ayu Ary Pramita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The global deployment of COVID-19 vaccines, utilizing distinct viral vector and mRNA technologies, has been followed by reports of rare neuro-ophthalmic adverse events, including optic neuritis (ON). This study aimed to systematically compare the clinical phenotypes, autoimmune serological profiles, and visual outcomes of ON cases with onset in temporal association with viral vector versus mRNA COVID-19 vaccination. Methods: A systematic review was conducted across PubMed, Scopus, and EMBASE databases for case reports and case series published up to August 2025 detailing ON after COVID-19 vaccination. Data were extracted on clinical presentation, MRI findings, serostatus for aquaporin-4 (AQP4-IgG) and myelin oligodendrocyte glycoprotein (MOG-IgG) antibodies, treatments, and visual outcomes. Separate meta-analyses of proportions and comparative odds ratios (OR) were calculated for key outcomes, including distinct analyses for NMOSD and MOGAD. Results: Our analysis of published reports included 20 studies, comprising 90 patients (40 viral vector, 50 mRNA). Cases associated with viral vector vaccines had significantly higher odds of presenting with bilateral disease (OR 4.31, 95% CI [1.67, 11.11]). This platform was also associated with markedly increased odds of AQP4-IgG positivity (NMOSD) (OR 5.15, 95% CI [1.35, 19.61]) and MOG-IgG positivity (MOGAD) (OR 4.58, 95% CI [1.09, 19.21]). Consequently, these patients had higher odds of requiring aggressive immunotherapy and of suffering incomplete visual recovery (OR 3.41, 95% CI [1.14, 10.21]). Conclusion: Our analysis of published case reports suggests that while ON following COVID-19 vaccination is a very rare event, its clinical phenotype may differ based on the vaccine platform. Cases associated with viral vector vaccines appear more likely to manifest as a severe, bilateral, antibody-mediated condition characteristic of NMOSD or MOGAD. These findings, which do not establish causality, underscore the critical importance of prompt autoantibody testing to guide appropriate management. The established benefits of vaccination continue to overwhelmingly outweigh the exceptionally low absolute risk of such adverse events.